2023
DOI: 10.3390/v15051074
|View full text |Cite
|
Sign up to set email alerts
|

Mpox Person-to-Person Transmission—Where Have We Got So Far? A Systematic Review

Abstract: The recent multi-country outbreak of Mpox (Monkeypox disease) constituted a public health emergency. Although animal-to-human transmission is known to be the primary way of transmission, an increasing number of cases transmitted by person-to-person contact have been reported. During the recent Mpox outbreak sexual or intimate contact has been considered the most important way of transmission. However, other routes of transmission must not be ignored. The knowledge of how the Monkeypox Virus (MPXV) spreads is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This observation confirmed the high plausibility of non-sexual transmission within a household beyond sexual transmission. 10 Our situational analysis did not reveal any evidence of this route of transmission within households before this investigation. So, this investigation was the first to document non-sexual transmission of mpox in Thailand, mirroring a similar occurrence in a hospital setting in the Republic of Congo.…”
Section: Discussionmentioning
confidence: 61%
“…This observation confirmed the high plausibility of non-sexual transmission within a household beyond sexual transmission. 10 Our situational analysis did not reveal any evidence of this route of transmission within households before this investigation. So, this investigation was the first to document non-sexual transmission of mpox in Thailand, mirroring a similar occurrence in a hospital setting in the Republic of Congo.…”
Section: Discussionmentioning
confidence: 61%
“…To spread MPXV, all it takes is direct contact with a patient's lesions, respiratory secretions, or infected things like clothing or bedding. There is currently a low level of threat among the general population ( Pinto et al, 2023 ). Despite the fact that the risks of healthcare-associated illnesses have not yet been identified for this outbreak, nurses who come into contact with infected patients should prevent infections by taking appropriate personal safety measures, including wearing adequate PPE ( Ren et al, 2022 ).…”
Section: Brief Reviewmentioning
confidence: 99%
“…People at highest risk tended to be those living in endemic rural communities, 44,48 those in close contact with infected animals, 27,48 people who hunted, ate, or handled infected wild animals, 42,46 those who travelled to endemic regions, 50,51 people who had not received the smallpox vaccine (which provides cross-protection), 57,58 and healthcare workers involved in diagnosing, treating, and caring for Mpox patients. 59,60 By contrast, in the 2022 Mpox outbreak, individuals in the European and American continents were primarily affected. They had little or no connection with endemic regions or contact with infected animals.…”
Section: Who Was At Risk Of Getting Monkeypox?mentioning
confidence: 99%
“…Although everyone is potentially susceptible to infection with the Mpox virus, survey of confirmed or suspected cases over the last 50 years, indicated that certain groups were primary affected. People at highest risk tended to be those living in endemic rural communities, 44,48 those in close contact with infected animals, 27,48 people who hunted, ate, or handled infected wild animals, 42,46 those who travelled to endemic regions, 50,51 people who had not received the smallpox vaccine (which provides cross‐protection), 57,58 and healthcare workers involved in diagnosing, treating, and caring for Mpox patients 59,60 . By contrast, in the 2022 Mpox outbreak, individuals in the European and American continents were primarily affected.…”
Section: Who Was At Risk Of Getting Monkeypox?mentioning
confidence: 99%